Conceptual framework of equity-focused implementation research for health programs (EquIR) - J. Eslava-Schmalbach; N. Garzón-Orjuela; V. Elias; L. Reveiz; N. Tran; E. V. Langlois (BMC, 2019)
Abstract Background Implementation research is increasingly used to identify common implementation problems and key barriers and facilitators influencing efficient access to health interventions. Objective To develop and propose an equity-based framework for Implementation Research (EquIR) of health programs, policies and systems. Methods A systematic search of models and conceptual frameworks involving equity in the implementation of health programs, policies and systems was conducted in Medline (PubMed), Embase, LILACS, Scopus and grey literature. Key characteristics of models and conceptual frameworks were summarized. We identified key aspects of equity in the context of seven Latin American countries-focused health programs We gathered information related to the awareness of inequalities in health policy, systems and programs, the potential negative impact of increasing inequalities in disadvantaged populations, and the strategies used to reduce them. Results A conceptual framework of EquIR was developed. It includes elements of equity-focused implementation research, but it also links the population health status before and after the implementation, including relevant aspects of health equity before, during and after the implementation. Additionally, health sectors were included, linked with social determinants of health through the "health in all policies" proposal affecting universal health and the potential impact of the public health and public policies. Conclusion EquIR is a conceptual framework that is proposed for use by decision makers and researchers during the implementation of programs, policies or health interventions, with a focus on equity, which aims to reduce or prevent the increase of existing inequalities during implementation.